Identification of DOT1L inhibitor in a screen for factors that promote dopaminergic neuron survival - Cui, Jun; Carey, Joseph; Reijo Pera, Renee A. (Frontiers in Aging Neuroscience, 2022)
Parkinson’s disease (PD) is a common neurodegenerative disorder characterized by the progressive loss of dopaminergic (DA) neurons in the substantia nigra region of the midbrain. Diagnostic criteria for PD require that at least two of three motor signs are observed: tremor, rigidity, and/or bradykinesia. The most common and effective treatment for PD is Levodopa (L-DOPA) which is readily converted to DA and has been the primary treatment since the 1960’s. Dopamine agonists have also been developed but are less effective than L-DOPA. Although the lack of a model system to study PD has hampered efforts to identify treatments, diverse screening strategies have been proposed for identification of new pharmaceutical candidates. Here, we describe a pilot screen to identify candidate molecules from a bioactive compound library, that might increase formation, maintenance and/or survival of DA neurons in vitro. The screen used a previously characterized reporter construct consisting of the luciferase gene inserted downstream of the endogenous tyrosine hydroxylase (TH) gene and neurons differentiated from human pluripotent stem cells for 18 days. The reporter mimics expression of TH and includes a secreted luciferase whose activity can be measured non-invasively over multiple timepoints. Screening of the bioactive compound library resulted in the identification of a single molecule, SGC0946, that is an inhibitor of DOT1L (Disruptor Of Telomeric silencing 1-Like) which encodes a widely-conserved histone H3K79 methyltransferase that is able to both activate and repress gene transcription. Results indicate that SGC0946 increased reporter luciferase activity with a single treatment at 8-hours post-plating being equivalent to continuous treatment. Moreover, data suggested that the total number of neurons differentiated in the assays was comparable from experiment to experiment under different SGC0946 treatments over time. In contrast, data suggested that the survival and/or maintenance of DA neurons might be specifically enhanced by SGC0946 treatment. These results document the feasibility of a set of tools for exploration of small molecules that may impact DA neuron differentiation and/or maintenance. Results provide evidence in support of reports that indicate inhibition of DOT1L may play an important role in maintenance and survival of neural progenitor cells (NPCs) and their lineage-specific differentiation.